Forme di mediatizzazione dello sport in canzone: Identità e immaginario nei brani della Nazionale italiana di calcio - Bertoloni, Luca (Mediascapes journal, 2024)
In the Italian mediascape the song-form, once it enters the media system through various intermedial objectifications, contributes to the institutional and social-constructivist trajectories of mediatization, on the one hand responding to a broader media logic, and on the other contributing to the media construction of reality. In these terms, its presence can also be tested in the specific mediatization of sport, within which it is shown along three levels: participating directly and transmedially in sportive events; collaborating on a paratextual level in the medial narration of the competitions; directly both recounting events, exploits and the lives of athletes, or making a metaphorical and conceptual synthesis of the essence of a sport.In Italy, the phenomenon is mainly attested with football and cycling. In particular, the songs related to the Italian national football team, moving on these three levels, are placed at the crossroads of a complex narrative, interweaving different elements and acting as a narrative device that contributes to the media storytelling of the national team's matches, especially the Word Cup, through both top-down and bottom-up logics. We identify four phases in which this particular form of sports mediatization manifests itself: the phase of ‘obsessions’, which goes from 1970 to 1990; that of ‘Notti magiche’, it began with the World Cup of Wonders in 1990 and then settled permanently in the cultural landscape; that of the ‘Anthems’, which goes from 1994 to 2014; and the actually dispersive ‘fragmentation’, which is observed from 2014 to today. The mediatization of the football in these stages have thus represented over time a textual element of cohesion and configuration of the national team's imaginary, through a solicitation of not only sporting, but also social and identity needs, especially when the songs are shared by practices of re-appropriation from below that are really shared by the public, even going so far as to replace Mameli's anthem on an identity and configuration level. In this way, football as a mediated sport shows its inherently a-political character and its profound nature as a social connector.